Reduction in expenditures on analgesics during one year of treatment of chronic tension headache with BoNT-A - Coloprisco, Gabriella (Springer-Verlag, 2003)
The aim of this study was to investigate the impact of the use of botulinum toxin type A (BoNT-A; BOTOX; Allergan, Inc.; Irvine, CA) as preventive treatment of chronic tension-type headache (CTH) on analgesic use and expenditure. This was a prospective, single-center, 1-year, open-label study of the effect of BoNT-A treatment on acute analgesic use and expenditure in CTH patients. A structured headache questionnaire, which included questions about medication costs, was completed by CTH patients attending a specialist headache clinic in Rome prior to BoNT-A injections. Repeat injections were administered every 3 months for up to 1 year. Patients were required to complete the questionnaire prior to each injections cycle. A pharmacoeconomic analysis was performed at each assessment to determine the effect of BoNT-A treatment on analgesic use and expenditure. Three hundred questionnaire were distributed and 296 (98%) were completed. The study population consisted of 67.8% (201) females and 32.2% (95) males, with a mean age of 46.7±16.1 years. The economic evaluation of the pharmacologic treatment of CTTH was conducted on the 101 (34.12%) patients who gave complete information on posology. Pharmacoeconomic data analysis focused on the whole group using analgesics compared to those who self-prescribed and those who turned to health specialists before and after treatment with BoNT-A. Prior to treatment with BoNT-A the median monthly pharmaceutic expenditure per patient was euro (€) 24.30 for the whole group using analgesics, and € 34.93 and € 18.51 for the “self-prescribers” and the “prescribed by specialist” groups, respectively. Median monthly pharmaceutic expenditure decreased significantly for the whole group (p<0.001), the ”self-prescribers” (p<0.01), and the “prescribed by specialist” group (p<0.002) (3rd month: € 13.3, 9.3, 7.2, respectively; 6th month: € 8.9, 9.0, 4.1, respectively; 9th month: € 5.7, 12.4, 3.0, respectively; 12th month € 4.1, 9.8, 3.4, respectively). BoNT-A treatment produced significant reductions in both analgesic use and expenditure. The data suggest that consultation with a specialist would be helpful in patients with CTTH. Cooperative studies on cost analysis of chronic daily headaches, including both CTTH and chronic migraine, comparing the economic cost package borne by patient and community both before and after treatment with BoNTA, are warranted. However, in the near future additional studies to compare clinical efficacy of BoNT-A in CTTH with its painkiller use/expenditure in the control of pain are needed in order to avoid any possible interference due to placebo effect.